PENDAMPINGAN PARTISIPATIF PRAKTIK PEMBELAJARAN BERMAKNA DI MADRASAH TSANAWIYAH NEGERI 6 NGANJUK - Badrus; Mohammad Auza'i Aqib (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This mentoring aims to provide guidance to MTsN 6 Nganjuk educators so that they can design and carry out meaningful learning, starting from opening learning, teaching practice in class and closing learning. This mentoring approach uses the participatory action research (PAR) method. The results of this mentoring show that meaningful learning mentoring is very beneficial for providing in-depth understanding to a number of existing educators, both theoretically and practically, starting from learning planning design, meaningful learning practices, mastery of motivation, direction accuracy, and how to give simple assignments to students. It is hoped that the results of this mentoring will become a learning model for educators in other educational institutions to create meaningful learning whose results can be felt by students. Keywords: Meaningful Learning, MTsN 6 Nganjuk Educators. Abstrak. Pendampingan ini bertujuan untuk memberikan pengarahan pendidik MTsN 6 Nganjuk agar dapat merancang dan melakukan pembelajaran bermakna, mulai dari membuka pembelajaran, praktik mengajar di kelas dan menutup pembelajaran. Pendekatan Pendampingan ini menggunakan metode partisipatori action research (PAR). Hasil pendampingan ini menunjukkan bahwa pendampingan pembelajaran bermakna sangat besar manfaatnya untuk memberikan pemahaman secara mendalam kepada sejumlah pendidik yang ada, baik teoritis maupun praktis, mulai dari desain perencanaan pembelajaran, praktik pembelajaran bermakna, penguasan motivasi, ketepatan pengarahan, dan cara memberi tugas yang simpel kepada peserta didik. Diharapkan hasil pendampingan ini menjadi model pembelajaran pendidik di lembaga pendidikan lain untuk menciptakan pembelajaran bermakna yang hasilnya bisa dirasakan oleh peserta didik. Kata Kunci: Pembelajaran Bermakna, Pendidik MTsN 6 Nganjuk.